Comparative Transcriptome Profiling Reveals Defense-Related Genes Against Ralstonia solanacearum Infection in Tobacco - Pan, Xiaoying; Chen, Junbiao; Yang, Aiguo; Yuan, Qinghua; Zhao, Weicai; Xu, Tingyu; Chen, Bowen; Ren, Min; Geng, Ruimei; Zong, Zhaohui; Ma, Zhuwen; Huang, Zhenrui; et al. (Frontiers in Plant Science, 2021)
Bacterial wilt (BW) caused by R. solanacearum (Ralstonia solanacearum), is a vascular disease of diverse solanaceous crops, causing tremendous damage to crop production. However, our knowledge of the mechanism underlying resistance or susceptibility to the disease is very limited. In this study, we characterized the physiological differences and compared the defense-related transcriptomes of two tobacco varieties, 4411-3 (Resistant, R) and K326 (Susceptible, S), before and after R. solanacearum infection at three time points (0, 10, and 17 dpi). We identified 3967 differentially expressed gene (DEGs) between the basal transcriptomes of the R and S genotypes at three time points, including1395 up-regulated genes in the R genotype and 2640 up-regulated genes in the S genotype. Next, we found 6,233 and 21,541 DEGs induced in the R and S genotypes, respectively, at three time points in response to R. solanacearum infection. Furthermore, GO and KEGG analyses revealed that DEGs in the R genotype before or after R. solanacearum infection were related to the cell wall, starch and sucrose metabolism, glutathione metabolism, ABC transporters, endocytosis, glycerolipid metabolism, and glycerophospholipid metabolism. The defense-related genes (e.g., genes related to the cell wall and genes encoding GSTs) generally showed genotype-specific regulation and expression differences before or after R. solanacearum infection. In addition, genes related to auxin and ABA were dramatically up-related in the R genotype. The contents of IAA and ABA in the S genotype were significantly higher than those in the R genotype after R. solanacearum infection, providing insight into the defense mechanisms of tobacco. Taken together, these results clarify the physiological and transcriptional regulation of resistance to R. solanacearum infection, improving our understanding of the molecular mechanism underlying the plant-pathogen interaction.